Abstract 215: A Sweet Indicator: HbA1C and Thrombectomy Outcomes in Hispanics - Zorain M. Khalil; Samantha D. Miller; Yazan D. Abualnadi; Sohum K. Desai; Kaiser O. Sadiq; Wondwossen G. Tekle; Ameer E. Hassan (Stroke: Vascular and Interventional Neurology, 2023)
Introduction There is a higher prevalence of diabetes mellitus type 2 in Hispanics as compared to other ethnic groups in the United States. Diabetes is a risk factor for acute ischemic stroke and also a poor predictor of outcome for many interventional surgeries. We performed this retrospective cohort analysis to assess the impact of poorly controlled diabetes, defined as HbA1C of 9.0% or greater, on the functional and procedural outcomes of Hispanic patients with acute ischemic stroke undergoing mechanical thrombectomy. Methods We conducted a retrospective review of a prospectively maintained patient database at a large volume comprehensive stroke center. Patients included were of Hispanic origin presenting between 2012 and 2022 who underwent thrombectomy for acute ischemic stroke. Baseline patient demographics and clinical characteristics recorded include age, gender, HbA1C level, National Institutes of Health Stroke Scale (NIHSS) at admission, manual CT ASPECTS and stroke risk factors (hypertension, atrial fibrillation, coronary artery disease, congestive heart failure, LDL, smoking, history of stroke/TIAs). Patients were separated into two groups depending on the presence poorly controlled diabetes defined as an HbA1C of 9.0% or greater. Outcomes evaluated include modified Rankin scale at 3 months, symptomatic intracranial hemorrhage, mass effect, 90‐day mortality, and whether any stenting or angioplasty was required during mechanical thrombectomy. Results 495 patients met the inclusion criteria out of which 69 had HbA1c of 9% or greater. Patients with poorly controlled diabetes were significantly younger (median age 63 vs 72, p <0.001), had a lower prevalence of atrial fibrillation (7.69% vs 29.8%, p <0.001) and a higher median LDL level (95.5 vs 72, p<0.001) compared to patients who did not have poorly controlled diabetes. Median NIHSS on admission was also lower in the poorly controlled diabetics group (13 vs 17, p = 0.02). There was a statistically significant lower rate of functional independence (mRS 0‐2) at 90 days in patients with poorly controlled diabetes (30.6% vs 45.3%, p=0.05) after adjusting for age, NIHSS, and atrial fibrillation. Patients with poorly controlled diabetes also were more likely to require angioplasty (31.3% vs. 20.5%; p = 0.048) and stenting (28.4% vs. 18.1%; p = 0.049) during mechanical thrombectomy. Conclusion High HbA1c levels upon admission may be used to predict poor functional outcomes of thrombectomy and may also be associated with a greater chance of patients requiring angioplasty and/or stenting during thrombectomy. This can assist the physician in deciding if thrombectomy should be done on a patient with poorly controlled diabetes.